2021
DOI: 10.1186/s12885-021-08818-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C3 and FN1 as potential biomarkers associated with progression and prognosis for clear cell renal cell carcinoma

Abstract: Background Clear cell renal cell carcinoma (ccRCC) is one of the most lethal urological malignancies, but the pathogenesis and prognosis of ccRCC remain obscure, which need to be better understand. Methods Differentially expressed genes were identified and function enrichment analyses were performed using three publicly available ccRCC gene expression profiles downloaded from the Gene Expression Omnibus database. The protein-protein interaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…Conversely, high CD59 expression is associated with better outcomes ( 29 , 80 , 122 ). Further support for the role of C3 in RCC comes from Dong and colleagues, who demonstrated that high mRNA and protein expression levels of C3 and fibronectin 1 (FN1) in cancer cells were primarily responsible for RCC tumorigenesis and progression ( 123 ). Furthermore, increased expression of C3 was also associated with the advanced clinical stage, high pathological grade, and poor survival.…”
Section: Complement Utility As Biomarkermentioning
confidence: 99%
“…Conversely, high CD59 expression is associated with better outcomes ( 29 , 80 , 122 ). Further support for the role of C3 in RCC comes from Dong and colleagues, who demonstrated that high mRNA and protein expression levels of C3 and fibronectin 1 (FN1) in cancer cells were primarily responsible for RCC tumorigenesis and progression ( 123 ). Furthermore, increased expression of C3 was also associated with the advanced clinical stage, high pathological grade, and poor survival.…”
Section: Complement Utility As Biomarkermentioning
confidence: 99%
“…CAF-induced fibronectin promotes the proliferation and inhibits the apoptosis of precancerous bronchial epithelial and carcinoma cells through the activation of PI3K/AKT signaling in the lung . As for RCC patients, higher fibronectin 1 expression showed an increased disease-related mortality rate (Steffens et al, 2012) and a more advanced clinical stage (Dong et al, 2021). Competing endogenous RNA networks further proved the direct correlations between FN1 and C3, FN1 and pro-fibrotic signaling pathways, including WNT, HIF, PI3K/AKT, MAPK, and TGF-β pathways, in ccRCC (Dong et al, 2021).…”
Section: Figurementioning
confidence: 78%
“…As for RCC patients, higher fibronectin 1 expression showed an increased disease-related mortality rate (Steffens et al, 2012) and a more advanced clinical stage (Dong et al, 2021). Competing endogenous RNA networks further proved the direct correlations between FN1 and C3, FN1 and pro-fibrotic signaling pathways, including WNT, HIF, PI3K/AKT, MAPK, and TGF-β pathways, in ccRCC (Dong et al, 2021). The TGF-β1/Src axis is a well-studied pro-fibrotic signaling pathway that promotes renal fibrosis and tumor progression by promoting macrophage-tomyofibroblast transition (MMT) (Meng et al, 2016;Tang et al, 2018).…”
Section: Figurementioning
confidence: 95%
“…31 The aberrant expression of FN1 has been proven to be associated closely with the invasion and prognosis of a variety of solid tumors, including renal, gastric, and lung cancers. 32,33 FN1 upregulation was strongly associated with M2 macrophage polarization and might be implicated in the progression of HNSCC through the Akt and MAPK signaling pathways. 34 Besides, Zhang et al demonstrated that FN1 increased the sensitivity of OS cells to cisplatin to promote cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%